Geopolitics of the Illicit Linking the Global South and Europe - Brombacher, Daniel; Maihold, Günther; Müller, Melanie; Vorrath, Judith (Weltwirtschaft und internationale Zusammenarbeit, 2022)
This anthology examines different dimensions of illicit commodity flows and asks how they can be understood through a geographical lens that looks from the Global South to Europe. By applying a supply chain perspective, it generates insights into how illegal, grey and legal markets merge at certain points in the production chain. This volume seeks to promote a holistic view through a 'thick description' of the specific flows and develops practical policy recommendations. It brings together contributions from authors from a wide range of backgrounds, including international scholars, journalists and specialists in both law enforcement and development cooperation. With contributions by Lorenzo Bagnoli; Stefan Bauchwitz, PhD; Dr. Dyhia Belhabib; Daniel Brombacher, Inga Carry; Peter Fabricius; Prof. Dr. Gerardo Damonte; Dr. Nhomsai Hagen, PhD; Dr. Cathrin Hauk, PhD; Prof. Dr. Lutz Heide, PhD; Prof. Dr. Philippe Le Billon, PhD; Prof. Dr. Günther Maihold; Fatjona Mejdini; Dr. Melanie Müller; Dr. Bettina Schorr; Jan Schubert; Ina Tessnow-von Wysocki; Dr. Leopold von Carlowitz and Dr. Judith Vorrath.